Exploring Wild Alabama : A Guide to the State's Publicly Accessible Natural Areas - Wills, Kenneth M. (Kenneth Malcolm), 1969- (Book collections on Project MUSE., 2016)
"Exploring Wild Alabama is an exceptionally detailed guide to the most beautiful natural destinations in the state. From the rocky outcrops of the Appalachian plateaus to the sugar-white beaches of the Gulf Coast's Orange Beach and Dauphin Island, Alabama offers a wealth of remarkable sites to explore by car or canoe, bicycle or motorcycle, or on foot. Intrepid explorers Kenneth M. Wills and L.J. Davenport divide Alabama into eleven geographic regions that feature state parks and preserves, national monuments and forests, wildlife management areas, Nature Conservancy and Forever Wild properties, botanical gardens and arboreta, as well as falls, caverns, and rock cliffs. Exploring Wild Alabama provides detailed site entries to one hundred and fifty destinations. Each section is beautifully illustrated with color photographs and area maps. Exploring Wild Alabama includes a large state map and numerous local topographic maps to help readers locate each site. Individual site entries include written directions to each site and GPS coordinates; engaging notes about the ecology, landscape features, and local species of plants and animals of the sites; and international recreation symbols for hiking, fishing, boating, camping, hunting, and other fun outdoor activities. Wills and Davenport guide travelers to Alabama jewels such as Sand Mountain's Chitwood Barrens, which harbors the rare Green Pitcher Plant and other exotic botanical species; Blowing Springs Cave in Lauderdale County, named for the cool air and the clear spring flowing out of the cave opening; Jackson Prairies in the Lime Hills region; and Booker's Mill in Conecuh County, offering diverse habitats and historic structures. Long a favorite destination for outdoor sports enthusiasts, Alabama is fast becoming a major 'ecotourism' destination, with thousands of travelers discovering the state's unsung natural treasures. Exploring Wild Alabama will be used and trusted by anyone who loves the outdoors--birders, botanists, cave explorers, cyclists, hunters, fishermen, rock climbers, canoeists, teachers, and other outdoor enthusiasts"--